High power conversion efficiencies and scaling issues for multimode vertical-cavity top-surface-emitting lasers - Chalmers, S. A., author; Kilcoyne, Sean Patrick, author; Lear, Kevin L., author; IEEE, publisher (Colorado State University. Libraries, 1994)
We report advances in the power conversion efficiencies of vertical-cavity top-surface-emitting lasers defined by proton implantation. Efficiencies as high as 13.4% and 15.8% have been obtained for single-mode and multimode operation, respectively. Scaling issues are addressed including the size dependence of threshold current, series resistance, lasing output power, and power conversion efficiency. We find that devices between 15 μm and 25 μm diameters show the highest power conversion efficiency due to the threshold current not scaling with the conductance and output power. Device geometries with contact apertures both equal to and less than (overlapping) the active region diameter were investigated.
Keywords: laser modes; laser cavity resonators; electric current; power conversion; semiconductor lasers